Gambaran Gejala Pada Pasien COVID-19 Dengan Komorbid, Di RSUD Labuang Baji Makassar - Ferly Yacoline Pailungan; Halbina Famung Halmar; Maria Kurnyata Rante Kada; Rasdin Rasdin; Fransiska Febriana (Sekolah Tinggi Ilmu Kesehatan Kesdam IX/Udayana, 2022)
Background: Corona virus disease 2019 is a disease caused by infection with the SARS-CoV-2 virus, which generally attacks the respiratory system in humans, Corona Virus disease can cause different symptoms, be it mild, moderate to severe symptoms. The level of symptoms in Corona Virus disease patients is influenced by various factors, both internal and external, and one of the influencing factors is the presence of comorbidities or comorbidities. The purpose of this study was to find out the description of symptoms in Corona Virus disease patients with comorbidities at Labuang Baji Hospital, Makassar City Method The research design used is descriptive analytic through a cross-sectional approach. The total population in this study was 129 people. The sampling technique used was total sampling.. Results: In this study, the results showed that of 129 Corona virus disease patients, most of them had comorbid cardiovascular disorders (hypertensive heart disease) and of all patients who had comorbidities, most of the respondents (48.1%) experienced severe symptoms. Conclusion: From this study it can be concluded that patients who have comorbid cardiovascular disease are more likely to experience severe symptoms when exposed to the corona virus.